Defining skills and knowledge for successful property Managers - Arif, Mohd Zaki; Yusof, Nor’Aini (2008)

(untitled)
The developments in landed properties have increased the demand for Property Managers. With the introduction of newer and modern building technology, has changed the roles and functions of property managers. Practicing property management in difference countries are subjected to the local rules and regulations. These are to ensure only proficient property managers are allow to practice property management. In Malaysia property managers are required to register with The Malaysia Board of Valuer and Estate Agent. However protest frequently emerges in the mass media, focusing on prominence area such as technical knowledge, skills, attitude and abilities of the property managers. To this degree incite the needs to define the skills and knowledge required by property managers to excel in property management. We hope to uncover these competencies and induce the property management practitioner to take up this substance to enhance their profession.